Variable-based analysis for traceability in QVT-R model transformations - Martínez Grassi, Omar Armando
Model-driven software development promotes models as the primary artifacts in software development. During all development phases, different models of the system are created, refined, and linked, such that from the requirements to the implementation a whole network of models is built. OMG's "Model-driven Architecture (MDA) is one important instance of this general paradigm, with a particular stress on automation of model creation and linkage. Models are complemented by model transformations written in the QVT language, describing how one model can be derived from another one. Traceability data in the MDA can be understood as the runtime footprint of model transformations. It has many applications: to perform change impact analysis, to keep consistency between models, to carry out requirement coverage analysis, etc. In this paper we present a proposal to enhance the retrieval of traceability information in MDA. The contributions of our work include the minimization of manual efforts to achieve traceability, as error-prone and time-consuming activity, and the attainment of independence regarding the QVT engine implementation.